Investigation Of Phosphorus Spin On Dopant On SOI Wafer - Tang, Yi Tian (Universiti Sains Malaysia, 2022)
Silicon on insulator (SOI) wafer has made it possible for the integrated circuit sector to develop superior, high-performance of semiconductor device and doping techniques are essential in forming the PN junction for semiconductor device. There are two most common doping techniques which is chemical vapour deposition and ion implantation. In this research study new doping method which is thermal diffusion using spin on dopant is introduced. The spin on dopant technique is an alternative technique that involves spinning a dopant-containing solution onto silicon on insulator wafers. The aim of this research work is to investigate the effect of thermal diffusion temperature and soaking time on its sheet resistance. In addition, doping uniformity also been investigated by using mapping techniques. Three inches boron-doped silicon on insulator wafer were cut and undergo Radio Corporation of America (RCA) standard cleaning. Filmtronics spin on dopant (SOD) P509 served as N-type dopants placed on silicon on insulator wafer for 40 seconds at 4,000 rpm using a spin coater. Thermal diffusion temperature and soaking time were set from 700oC to 1000oC and 30 to 120 minutes, respectively. After thermal diffusion, samples were etched with hydrofluoric acid (HF). All samples were characterized by four point probe, Hall Effect and Atomic Force Microscopy (AFM). The increase of thermal diffusion soaking time reduces sheet resistance until activated dopants are saturated at 900°C. When sheet resistance decreased, the concentration of dopants increased. Temperature and soaking time enhanced the carrier density and surface roughness but reduced Hall mobility. Mapping techniques showed that low non-uniformity value which was less than 10% suggested good thermal diffusion control.